Structure Analysis and Heat Transfer Performance Study on Spiral Plate of the Adsorption Bed - Chen Huanxin; Wei Li; Zhang Wei; Dong Yuanyuan; Zhu Jing; Zhang Chuo; Yin Ming (Zhileng xuebao)
The advantages and disadvantages of the spiral plate adsorption bed are analyzed. The heat transfer process and the demand of cold and heat sources in a spiral plate adsorption bed, which is designed with counter-flow heat transfer and based on 15kW refrigerating output, are theoretically analyzed and optimized. The result shows that the heat-transfer capability of the spiral plate adsorption bed is better and its volume is smaller than other adsorption beds. If the processing difficulties and settings of mass transfer channel can be solved effectively, the spiral plate adsorption bed can be widely used, which will benefit the commercialization of the technology.